Accounting Relations in Bilateral Value Added Trade - Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2013)
Abstract The increasing international fragmentation of production has triggered the development of a number of widely used indicators accounting for value added flows in the world economy. This paper generalises these measures by simultaneously considering the import side and focusing on bilateral gross and value added trade flows. It discusses how these indicators relate to each other, the role of double counting in bilateral value added trade, and aggregation issues in global value added flows. Using the World Input-Output Database (WIOD) selected results on bilateral value added trade for the EU 27 countries, the United States and China over the period 1995-2011 are presented.
Keywords: F1; F15; F19; 330; production fragmentation; value added trade; vertical specialisation; bilateral trade